Chemical mechanical polishing composition and method for preventing clogging of polishing pad grooves
By using a chemical mechanical polishing composition with components such as bimodal distribution of colloidal silica particles and hydrolyzed polyvinyl alcohol, the problem of clogging of polishing pad grooves is solved and more uniform polishing and planarization effects are achieved.
Patent Information
- Application Number
- CN202410928431.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2024-07-11
- Publication Date
- 2025-01-24
AI Technical Summary
During chemical mechanical polishing and planarization, the grooves of the polishing pads are prone to clogging, resulting in a degradation of polishing uniformity performance.
A chemical mechanical polishing composition comprising water, an abrasive having a bimodal distribution of colloidal silica particles, 80% to less than or equal to 90% hydrolyzed polyvinyl alcohol, an electrolyte and a pH greater than 7 is used during the polishing process Polishing pad with polished surface and grooves.
Effectively suppress the blockage of polishing grooves, prevent the gradual offset of polishing uniformity performance, and improve the polishing and flat performance.
Smart Images

Figure CN119347637A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a chemical mechanical polishing composition and a method for preventing clogging of polishing pad grooves during chemical mechanical polishing and planarization. More specifically, the present invention relates to a chemical mechanical polishing composition and a method for preventing clogging of polishing pad grooves during chemical mechanical polishing and planarization, wherein the chemical mechanical polishing composition comprises water, an abrasive having a bimodal distribution of colloidal silica particles, the colloidal silica particles comprising elongated colloidal silica particles, 80% to less than or equal to 90% hydrolyzed polyvinyl alcohol, an electrolyte, a pH greater than 7 and good conductivity. Background Art
[0002] In the manufacture of integrated circuits and other electronic devices, multiple layers of conductive, semiconductive, and dielectric materials are deposited on or removed from the surface of a semiconductor wafer. Thin layers of conductive, semiconductive, and dielectric materials can be deposited by a variety of deposition techniques. Common deposition techniques in modern processing include physical vapor deposition (PVD) (also known as sputtering), chemical vapor deposition (CVD), plasma enhanced chemical vapor deposition (PECVD), and electrochemical plating (ECP).
[0003] As material layers are deposited and removed in sequence, the uppermost surface of the wafer becomes non-planar. Because subsequent semiconductor processing (e.g., metallization) requires the wafer to have a flat surface, the wafer needs to be planarized. Planarization can be used to remove unwanted surface topography and surface defects, such as rough surfaces, agglomerated materials, lattice damage, scratches, and contaminated layers or materials.
[0004] Chemical mechanical planarization, or chemical mechanical polishing (CMP), is a common technique for planarizing a substrate (such as a semiconductor wafer). In conventional CMP, a wafer is mounted on a carrier assembly and positioned to contact a polishing pad in a CMP apparatus. The carrier assembly provides a controllable pressure to the wafer, thereby pressing the wafer against the polishing pad. The pad is moved (e.g., rotated) relative to the wafer by an external driving force. At the same time, a polishing composition ("slurry") or other polishing fluid is provided between the wafer and the polishing pad. Therefore, the wafer surface is polished and made flat by the chemical and mechanical action of the pad surface and the slurry.
[0005] There is a great deal of complexity involved in CMP. Each type of material requires a unique polishing composition, an appropriately designed polishing pad, optimized process settings for both polishing and post-CMP cleaning, and other factors that must be individually tailored for the application of polishing a specific material.
[0006] A variety of abrasive particles can be used in the polishing or planarization process. Colloidal silica particles of different sizes are often the abrasive of choice for polishing and planarization of semiconductor wafers. In addition to size, the particles can also have a variety of shapes. Colloidal silica particles with round, oval, elongated, or nodular shapes are common. Elongated colloidal silica particles have become a popular choice for alkaline ILD slurries due to their improved polishing efficiency compared to other shapes of silica particles.
[0007] Some of the leading slurries used for polishing and planarizing semiconductor wafers contain elongated colloidal silica particles, which are usually in combination with colloidal silica particles of other shapes. However, a major problem associated with such slurries is that they may cause clogging of the pad grooves of several commercially available polishing pads after prolonged polishing. The shape of such pad grooves is typically annular. The consequence of pad groove clogging is a significant reduction in polishing uniformity performance. This is manifested by a gradual shift in polishing uniformity across the semiconductor wafer surface due to localized blockages in slurry delivery during the polishing process.
[0008] Figure 1A-Figure 1C It is made of water and ~12wt% Optiplane TM After polishing a semiconductor wafer with an aqueous chemical mechanical polishing slurry composed of 1735 abrasive colloidal silica particles, VisionPad TM Photo of the polishing surface (center to edge) of a 5000 polyurethane polishing pad. The colloidal silica particles include a mixture of spherical colloidal silica particles and elongated and nodular particles. The pH of the polishing slurry is ~10.7. The annular groove has a width of 8 mm, a depth of 2 mm, an outer edge radius of 340 mm, and an inner edge radius of 335 mm. Polishing at Applied Materials The polishing machine was run at a slurry flow rate of 100 mL / min, a down force of about 34.5 kPa, a platen speed of 108 rpm, and a carrier speed of 102 rpm.
[0009] Figure 1A-Figure 1C The degree of clogging of the annular groove disposed in the polishing surface of the pad base is shown, starting from near the center of the pad (e.g. Figure 1A , which shows a large amount of clogging of the groove), and continues to the part away from the center (as shown in Figure 1B , where the clogging of the grooves is slightly reduced), and then continues to the periphery of the pad (as shown in Figure 1C , where the grooves are substantially free of clogging). This illustrates a gradual deviation in polishing uniformity. The more the annular grooves are clogged, the more uneven the planarization of the semiconductor wafer surface becomes.
[0010] Therefore, there is a need for a chemical mechanical polishing slurry and method that inhibits polishing pad groove clogging while maintaining good polishing and planarization performance. Summary of the invention
[0011] The present invention provides a chemical mechanical polishing composition comprising water, an abrasive having a bimodal distribution of colloidal silica particles, the colloidal silica particles comprising elongated colloidal silica particles, 80% to less than or equal to 90% hydrolyzed polyvinyl alcohol, an electrolyte and a pH greater than 7.
[0012] The present invention further provides a chemical mechanical polishing composition comprising water, an abrasive having a bimodal distribution of colloidal silica particles, the colloidal silica particles comprising elongated colloidal silica particles, 80%-89% hydrolyzed polyvinyl alcohol, an electrolyte, a pH adjuster, and a pH of 8 to 12.
[0013] The present invention further provides a chemical mechanical polishing composition comprising water, an abrasive having a bimodal distribution of colloidal silica particles, the colloidal silica particles comprising elongated colloidal silica particles, 87%-89% hydrolyzed polyvinyl alcohol, an electrolyte, a pH adjuster, and a pH of 9 to 11.
[0014] The present invention also provides a method for chemical mechanical polishing of a substrate, the method comprising: providing a substrate, wherein the substrate comprises silicon oxide; providing a chemical mechanical polishing composition comprising water, an abrasive having a bimodal distribution of colloidal silica particles, the colloidal silica particles comprising elongated colloidal silica particles, less than 90% hydrolyzed polyvinyl alcohol, an electrolyte, and a pH greater than 7; providing a chemical mechanical polishing pad having a polishing surface and grooves; creating dynamic contact at an interface between the polishing surface of the chemical mechanical polishing pad and the substrate with a downforce of 20 to 100 kPa; and dispensing the chemical mechanical polishing composition onto the chemical mechanical polishing pad at or near the interface between the chemical mechanical polishing pad and the substrate; and wherein some of the silicon oxide is removed from the substrate.
[0015] Unexpectedly, a chemical mechanical polishing composition comprising water, an abrasive having a bimodal distribution of colloidal silica particles (including elongated colloidal silica particles), 80% hydrolyzed to less than or equal to 90% hydrolyzed polyvinyl alcohol, an electrolyte, and a pH greater than 7, and a method of polishing a substrate containing silica with a polishing pad containing grooves, inhibits undesirable clogging of the polishing pad grooves during chemical mechanical polishing. Inhibiting the clogging of the grooves substantially prevents a gradual shift in polishing uniformity across a semiconductor wafer surface due to localized blockage of slurry delivery, thereby enabling improved polishing and planarization performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1A A photograph taken with a Nikon SMZ 1500 stereo microscope of a portion near the center of the polishing surface of a VP5000 polyurethane polishing pad after polishing shows the annular grooves that were clogged with conventional polishing slurry.
[0017] Figure 1B Photographed with a Nikon SMZ 1500 stereo microscope. After polishing, away from IC1000 TM Photograph of a portion of the center of the polishing surface of a polyurethane polishing pad showing annular grooves that have become clogged with conventional polishing slurry.
[0018] Figure 1C IC1000 after polishing was photographed using a Nikon SMZ 1500 stereo microscope TM Photograph of a portion of the periphery of the polishing surface of a polyurethane polishing pad showing annular grooves that are substantially free of polishing slurry.
[0019] Figure 2A is a photograph taken with an iPhone of the polishing surface of a VP5000 polyurethane pad after polishing with the slurry of the present invention, showing a plurality of annular grooves without the polishing slurry.
[0020] Figure 2B is a photograph taken with a Nikon SMZ 1500 stereo microscope of a portion of the polishing surface of a VP5000 polyurethane pad after polishing with a slurry of the present invention, showing a plurality of annular grooves without the polishing slurry. DETAILED DESCRIPTION
[0021] As used throughout this specification, the following abbreviations have the following meanings, unless the context indicates otherwise: L = liter; mL = milliliter; kPa = kilopascal; nm = nanometers; cm = centimeters; mm = millimeters; g = grams; min = minutes; rpm = revolutions per minute; wt% = weight percent; RR = removal rate; PVA = polyvinyl alcohol; PS = polishing slurry of the present invention; PC = comparative polishing slurry; Mw = weight average molecular weight grams per mole; k = 1000; mS = milliSiemens; "~" = about; and VP5000 = VisionPad TM 5000 polyurethane polishing pad.
[0022] The term "chemical mechanical polishing" or "CMP" refers to a process in which a substrate is polished solely by chemical and mechanical forces and is distinguished from electrochemical-mechanical polishing (ECMP) in which an electrical bias is applied to the substrate. The term "TEOS" means a process made of tetraethyl orthosilicate (Si(OC 2 H 5 ) 4) decomposed from silica. The term "elongated" with respect to colloidal silica abrasive particles means that these abrasive particles have a length greater than their width. The term "spherical" with respect to colloidal silica particles means that the shape of these abrasive particles is round or circular. The term "bimodal distribution" means a set of scores having two (2) peaks or modes around which the values tend to cluster, so that the frequency around each peak first increases and then decreases, and when the peak heights are unequal, the higher vertex or peak is the primary mode and the lower peak is the secondary mode (for colloidal silica abrasive particles, it can be expressed on a Cartesian plane as the relative weight of the particles on the Y axis relative to the particle size in microns on the X axis, where the X axis is linear or preferably log). The term "multimodal" means having or involving multiple modes, patterns or maxima. The term "unimodal" or "unimodal" means a distribution having only one peak. The term "average value" refers to a value that falls between the first mode and the second mode (close to the second mode) and is the average value of the Cartesian plane diagram of the entire relative particle weight relative to the particle size in microns. As used in this specification, the term "dominant" means a bimodal particle distribution mode of abrasive colloidal silica particles, which has a dominant influence or is the most important mode of the bimodal particle distribution of abrasive colloidal silica particles during chemical mechanical polishing of the substrate. Throughout the specification, the terms "composition" and "slurry" are used interchangeably. The term "halide ion" means chloride ion, bromide ion, fluoride ion and iodide ion. The term "electrolyte" means a substance that decomposes into ions (charged particles) when it is dissolved in water. The term "Siemens (S)" is the international standard (SI) for conductivity. The term "one / kind (a / an)" refers to both the singular and the plural. Unless otherwise noted, all percentages are by weight. All numerical ranges are inclusive and combinable in any order, unless such numerical ranges are logically constrained to add up to 100%.
[0023] The chemical mechanical polishing composition of the present invention comprises elongated and spherical colloidal silica abrasive particles having a bimodal particle distribution. Preferably, the colloidal silica used contains at least one of precipitated silica and agglomerated silica. Preferably, the bimodal particle distribution of the colloidal silica abrasive particles exhibits a first mode with a first average particle size maximum of 50-100 nm, more preferably 60-90 nm, further preferably 70-90 nm, and most preferably 80-90 nm. Preferably, the elongated colloidal silica abrasive particles exhibit a second mode with a second average particle size maximum of 100-200 nm, more preferably 120-180 nm, further preferably 130-170 nm, even more preferably 140-165 nm, and most preferably 140-150 nm. The first mode reflects spherical particles, while the second mode indicates elongated particles. The second mode dominates the bimodal particle distribution.
[0024] Preferably, the mean value of the bimodal particle distribution is 95-200 nm, more preferably 110-180 nm, most preferably 135-165 nm. Preferably, the mean value falls between the first mode and the second mode (close to the second mode).
[0025] The chemical mechanical polishing composition of the present invention preferably comprises 5-30 wt% of colloidal abrasive silica particles, wherein 50 wt% and more of the colloidal abrasive silica particles are elongated colloidal abrasive silica particles. More preferably, the chemical mechanical polishing composition of the present invention comprises 10-30 wt% of colloidal abrasive silica particles, wherein 50-95 wt% of the colloidal silica abrasive particles are elongated abrasive silica particles, and even more preferably, the chemical mechanical polishing composition comprises 10-20 wt% of colloidal abrasive silica particles, wherein 70-90 wt% are elongated colloidal silica abrasive particles.
[0026] The colloidal silica abrasive particles of the present invention are a mixture of a first group of colloidal silica abrasive particles preferably having an average particle size of 75-80 nm and a second group of colloidal silica abrasive particles preferably having an average particle size of 110-140 nm.
[0027] An example of a commercially available colloidal silica abrasive comprising a bimodal distribution of elongated colloidal silica abrasive particles is Klebosol®, available from DuPont and manufactured by Merck KgAA, Darmstadt, Germany. TM 1635Colloidal silica.
[0028] The chemical mechanical polishing composition of the present invention comprises polyvinyl alcohol. The polyvinyl alcohol is formed by hydrolysis of polyvinyl acetate by methods known in the art. Preferably, the degree of hydrolysis of the polyvinyl alcohol is 80% to less than or equal to 90% hydrolyzed, more preferably, the polyvinyl alcohol is 80%-89% hydrolyzed, and most preferably 87%-89% hydrolyzed. The degree of hydrolysis refers to the ratio of the amount of free hydroxyl groups present on the polyvinyl alcohol to the sum of free hydroxyl groups and acetylated hydroxyl groups.
[0029] Preferably, the 80% to less than or equal to 90% hydrolyzed polyvinyl alcohol of the present invention has a weight average molecular weight of 9000 g / mole and greater, more preferably 10,000-200,000 g / mole, even more preferably 10,000-190,000 g / mole, further preferably 12,000-150,000 g / mole, and most preferably 30,000-50,000 g / mole.
[0030] Preferably, the polyvinyl alcohol is included in the chemical mechanical polishing composition of the present invention in an amount of 0.001-0.05 wt %, more preferably 0.0025-0.01 wt %, most preferably 0.005-0.01 wt %.
[0031] One or more inorganic or organic electrolytes are included in the chemical mechanical polishing composition of the present invention to provide the desired conductivity. Preferably, the conductivity of the chemical mechanical polishing composition of the present invention is 4 mS / cm and greater, more preferably 4-7 mS / cm, most preferably 5-7 mS / cm.
[0032] Inorganic electrolytes include, but are not limited to, alkali metal salts such as sodium chloride and potassium chloride, ammonium salts, alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, alkali metal bicarbonates such as sodium bicarbonate, phosphates such as potassium phosphate, nitrates such as potassium nitrate, sulfates such as potassium sulfate, and mixtures of the foregoing.
[0033] Organic electrolytes include, but are not limited to, choline chloride, carboxylic acids such as citric acid and acetic acid, quaternary ammonium salts such as benzyltrimethylammonium chloride, phenyltrimethylammonium chloride, phenyltrimethylammonium bromide, and phenyltrimethylammonium hydroxide. A mixture of the foregoing electrolytes may be included in the chemical mechanical polishing composition of the present invention.
[0034] Inorganic and organic electrolytes are included in the chemical mechanical polishing composition in an amount sufficient to obtain the desired conductivity. Preferably, the inorganic and organic electrolytes are included in an amount of at least 0.01 wt% and greater, more preferably 0.01-1 wt%, further preferably 0.05-0.25 wt%.
[0035] The chemical mechanical polishing composition used in the chemical mechanical polishing method of the present invention has a pH of >7, preferably 8-12, more preferably 9-11.
[0036] Optionally, the chemical mechanical polishing composition may include one or more pH adjusters to maintain the pH within a desired range. Preferably, the pH adjuster is selected from one or more of sodium hydroxide, potassium hydroxide, ammonium hydroxide, ammonium halide and nitrate.
[0037] Optionally, the chemical mechanical polishing composition contains a biocide such as KORDEK TM MLX (9.5%-9.9% methyl-4-isothiazolin-3-one, 89.1%-89.5% water and ≤1.0% of related reaction products) or KATHON containing the active ingredients 2-methyl-4-isothiazolin-3-one and 5-chloro-2-methyl-4-isothiazolin-3-one TMICP III, each manufactured by International Flavors & Fragrances, Inc. (KATHON and KORDEK are trademarks of International Flavors & Fragrances, Inc.).
[0038] When the biocide is included in the chemical mechanical polishing composition of the present invention, the biocide is included in an amount of 0.0001 wt % to 0.1 wt %, preferably 0.001 wt % to 0.05 wt %, more preferably 0.001 wt % to 0.01 wt %, still more preferably 0.001 wt % to 0.005 wt %.
[0039] The water contained in the chemical mechanical polishing composition used in the chemical mechanical polishing method of the present invention is preferably at least one of deionized water and distilled water to limit incidental impurities.
[0040] Preferably, the chemical mechanical polishing composition consists of water, an abrasive of bimodal distribution of colloidal silica particles (wherein the colloidal silica particles are elongated and spherical), 80% to less than or equal to 90% hydrolyzed polyvinyl alcohol, an electrolyte, optionally a biocide, optionally a pH adjuster, and a pH greater than 7.
[0041] More preferably, the chemical mechanical polishing composition consists of water, an abrasive of bimodal distribution of colloidal silica particles (wherein the colloidal silica particles are elongated and spherical), 87%-89% hydrolyzed polyvinyl alcohol, an electrolyte, optionally a biocide, optionally a pH adjuster, and a pH of 8-12.
[0042] Further preferably, the chemical mechanical polishing composition consists of water, an abrasive of bimodal distribution of colloidal silica particles (wherein the colloidal silica particles are elongated and spherical), 87%-89% hydrolyzed polyvinyl alcohol having a weight average molecular weight of 9000 g / mole or greater, an electrolyte, optionally a biocide, optionally a pH adjuster, and a pH of 9-11.
[0043] Most preferably, the chemical mechanical polishing composition consists of water, an abrasive of a bimodal distribution of colloidal silica particles, wherein the colloidal silica particles are elongated and spherical, polyvinyl alcohol that is 87%-89% hydrolyzed and has a weight average molecular weight of 12,000-150,000 grams / mole, an electrolyte, a conductivity greater than or equal to 4 mS / cm, optionally a biocide, optionally a pH adjuster, and a pH of 9-11.
[0044] The substrate to be polished in the chemical mechanical polishing method of the present invention comprises silicon oxide. The silicon oxide in the substrate includes, but is not limited to, borophosphosilicate glass (BPSG), plasma enhanced tetraethyl orthosilicate (PETEOS), tetraethyl orthosilicate (Si(OC 2 H 5 ) 4 ) formed by decomposition of silicon oxide, thermal oxide, undoped silicate glass, and high-density plasma (HDP) oxide.
[0045] The chemical mechanical polishing pad used in the chemical mechanical polishing method for removing silicon oxide of the present invention can be any suitable polishing pad known in the art. The chemical mechanical polishing pad can be optionally selected from a woven polishing pad and a non-woven polishing pad. The chemical mechanical polishing pad can be made of any suitable polymer having different density, hardness, thickness, compressibility and modulus. The chemical mechanical polishing pad used in the polishing method of the present invention includes a groove on the polishing surface, such as an annular groove. The size of the groove can vary. All grooves on a given pad can have the same size, or the grooves can vary in size. For example, in one embodiment, the annular groove can have a width of 3-8 mm, a depth of 0.5-2 mm, an outer edge radius of 335-340 mm, and an inner edge radius of 330-335 mm. In another embodiment, the groove can have a width of 3-8 mm, a depth of 0.5-2 mm, an outer edge radius of 35-45 mm, and an inner edge radius of 30-40 mm.
[0046] Commercially available polishing pads that can be used to practice the method of the present invention include, but are not limited to, VISIONPAD 5000 / K7 TM Polyurethane polishing pad, IC1000 TM Polyurethane polishing pad and IC1010 TM Polyurethane polishing pad (available from Rohm and Haas Electronic Materials CMP, LLC).
[0047] The chemical mechanical polishing composition used in the chemical mechanical polishing method of the present invention enables operation on a 300 mm polisher at a low nominal polishing downforce pad pressure (e.g., at 20 to 35 kPa) at a platen speed of 93-123 rpm, a carrier speed of 87-117 rpm, and a chemical mechanical polishing composition flow rate of 40-300 mL / min.
[0048] The chemical mechanical polishing composition and method of the present invention inhibits clogging of the grooves of the chemical mechanical polishing pad to enable uniform planarization of semiconductor wafers at a significant removal rate of TEOS from the wafer surface. For example, Figure 2A-2B is a photograph of the polishing surface of a VP5000 polyurethane polishing pad after polishing a semiconductor wafer with an aqueous chemical mechanical polishing slurry of the present invention, the aqueous chemical mechanical polishing slurry consisting of water and 11.5 wt % of KLEBOSOL TM 1635 abrasive colloidal silica particles, 0.005 wt% 89% hydrolyzed polyvinyl alcohol, 0.055 wt% benzyltrimethylammonium chloride, 0.055 wt% choline chloride and 0.164 wt% potassium carbonate, and pH 10.7. The colloidal silica particles include -90% elongated colloidal silica particles, and the remainder are spherical particles.
[0049] The annular groove has a width of 8 mm, a depth of 2 mm, an outer edge radius of 340 mm, and an inner edge radius of 335 mm. Polishing at Applied Materials The polishing machine was run at a slurry flow rate of 100 mL / min, a down force of about 34.5 kPa, a platen speed of 108 rpm, and a carrier speed of 102 rpm.
[0050] Figure 2A-2B An annular groove disposed in the polishing surface of the pad base is shown. Figure 2A A plurality of annular grooves in the polishing surface of the polishing pad base after polishing is shown, showing that all grooves are free of polishing slurry. Figure 2B is a closer image of the polishing pad surface where the grooves are free of polishing slurry.The chemical mechanical polishing compositions and methods of the present invention exhibit unexpected inhibition of polishing pad groove clogging.
[0051] The following examples are intended to illustrate the present invention but are not intended to limit its scope.
[0052] In the following examples, temperature and pressure conditions are ambient temperature and standard pressure unless otherwise indicated.
[0053] The following materials were used in the examples that follow:
[0054] Polishing removal rate experiments were conducted on 160 20.3 cm blank wafers. Applied Materials The polishing examples used a VISIONPAD 5000 / K7 with grooves 40 mil (1 mm) deep, 18 mil (0.45 mm) grooves and 120 mil (3 mm) spacing. TMA polyurethane polishing pad (available from Rohm and Haas Electronic Materials CMP, Inc.) was run at a downforce of 31.7 kPa (4.6 psi), a chemical mechanical polishing slurry composition flow rate of 100 mL / min, a table rotation speed of 108 rpm, and a carrier rotation speed of 102 rpm. The cleanliness of the grooves of the pad was visually observed before and after polishing. The TEOS removal rate was determined by measuring the film thickness before and after polishing using a KLA-Tencor FX200 metrology tool. During chemical mechanical polishing, the polishing slurry was maintained at a pH of approximately 10.7. A 2 wt % aqueous solution of KOH was added to each slurry to maintain the desired pH. The slurry conductivity was measured using a YSI 3200 conductivity meter (available from YSI Incorporated, Yellow Springs, Ohio 45387, USA). The CPS Disc Centrifuge TM The Nano Particle Size Analyzer (available from CPS Instruments, Inc., Stuart, FL) measures the mean and mode of the abrasive colloidal silica particles.
[0055] Example 1
[0056] Comparative Chemical Mechanical Polishing Compositions
[0057] Aqueous chemical mechanical polishing slurries were prepared as shown in Table 1 below.
[0058] Table 1
[0059]
[0060]
[0061] Abrasive: Klebosol available from DuPont, manufactured by Merck KGaA, Darmstadt, Germany TM 1635 bimodal colloidal silica particles containing 50 wt% elongated particles and the rest being spherical, ellipsoidal or nodular.
[0062] Table 2
[0063]
[0064] Klebosol TM 1635 bimodal colloidal silica particles together with organic and inorganic electrolytes produce a remarkable VISIONPAD 5000 / K7 TM The polyurethane polishing pad grooves are clogged. The polishing pad's annular grooves look essentially like Figure 2A-2B In contrast, the annular grooves of the comparative polishing pad appear essentially as in Figure 1A-1BAs shown in .
[0065] Example 2
[0066] Chemical mechanical polishing compositions, TEOS RR, and inhibition of pad groove clogging
[0067] Aqueous chemical mechanical polishing slurries were prepared as shown in Tables 3A and 3B below. Each chemical mechanical polishing slurry contained 11.5 wt % Klebosol TM 1635 Colloidal Silica Abrasive. Klebosol TM 1635 colloidal silica abrasive includes 50 wt% elongated particles.
[0068] Table 3A
[0069]
[0070] Table 3B
[0071]
[0072]
[0073] Table 4
[0074]
[0075] The polishing results show that the combination of elongated colloidal silica abrasive and 80%-89% hydrolyzed PVA with Mw ranging from 9000 to 186000 g / mol significantly prevents the VISIONPAD 5000 / K7 TM Clogging of Polyurethane Polishing Pad Grooves. Furthermore, the TEOS removal rates were as good as, if not better than, the TEOS removal rates of polishing compositions PC-1 to PC-6 of Example 1 above (which did not contain PVA).
[0076] Although PC-7 showed good TEOS removal rates, ~16 grooves were blocked. This indicates that 99% hydrolyzed PVA with a Mw of 146,000-186,000 g / mol is not effective in inhibiting the degradation of VISIONPAD 5000 / K7. TM Clogging of the grooves of polyurethane polishing pads is undesirable.
[0077] Example 3
[0078] Chemical mechanical polishing compositions, TEOS RR, and inhibition of pad groove clogging by (elongated vs. spherical) colloidal silica particles
[0079] Aqueous chemical mechanical polishing slurries were prepared as shown in Table 5 below.
[0080] Table 5
[0081]
[0082] Klebosol, available from DuPont, manufactured by Merck KGaA, Darmstadt, Germany TM 1501-50 Colloidal silica abrasive, which contains more than 80wt% spherical particles, and the rest are elongated, elliptical or nodular.
[0083] Table 6
[0084]
[0085] Although unimodal PC-8 has a higher TEOS removal rate than bimodal PS-11 and PS-12 containing electrolyte and 80% hydrolyzed PVA, PS-11 and PS-12 still show high TEOS removal rates. More importantly, PC-8 has some undesirable groove clogging, while PS-11 and PS-12 do not show groove clogging.
Claims
1. A chemical mechanical polishing composition comprising water, an abrasive having a bimodal distribution of colloidal silica particles, the colloidal silica particles comprising elongated colloidal silica particles, 80% to less than or equal to 90% hydrolyzed polyvinyl alcohol, an electrolyte, and a pH greater than 7.
2. The chemical mechanical polishing composition according to claim 1, wherein The polyvinyl alcohol is 80%-89% hydrolyzed.
3. The chemical mechanical polishing composition according to claim 2, wherein The polyvinyl alcohol is 87%-89% hydrolyzed.
4. The chemical mechanical polishing composition according to claim 1, wherein The weight average molecular weight of the 80% to less than or equal to 90% hydrolyzed polyvinyl alcohol is 9000 g / mole or greater.
5. The chemical mechanical polishing composition according to claim 4, wherein The weight average molecular weight is 12,000-150,000 g / mol.
6. The chemical mechanical polishing composition according to claim 1, wherein The amount of 80% to less than or equal to 90% hydrolyzed polyvinyl alcohol is 0.001-0.01 wt%.
7. The chemical mechanical polishing composition according to claim 1, wherein The chemical mechanical polishing composition has an electrical conductivity of 4 mS / cm and greater.
8. The chemical mechanical polishing composition according to claim 1, wherein The pH is 8-12.
9. The chemical mechanical polishing composition according to claim 1, wherein The bimodal distribution of elongated colloidal silica particles has a first mode with a first particle size maximum of 50-100 nm and a second mode with a second particle size maximum of 100-200 nm.
10. A method for chemical mechanical polishing of a substrate, the method comprising: Providing a substrate, wherein the substrate comprises silicon oxide; providing a chemical mechanical polishing composition, the chemical mechanical polishing composition consisting of: water, an abrasive having a bimodal distribution of colloidal silica particles, the colloidal silica particles comprising elongated colloidal silica particles, 80% to less than 90% hydrolyzed polyvinyl alcohol, an electrolyte, optionally a biocide, optionally a surfactant, optionally a pH adjuster, and a pH greater than 7; as well as Providing a chemical mechanical polishing pad having a polishing surface and grooves; generating dynamic contact at an interface between the polishing surface of the chemical mechanical polishing pad and the substrate with a downforce of 20 to 35 kPa; and dispensing the chemical mechanical polishing composition onto the chemical mechanical polishing pad at or near an interface between the chemical mechanical polishing pad and the substrate; and wherein some of the silicon oxide is removed from the substrate.
Citation Information
Cited By
Chemical mechanical polishing composition for polishing silicon oxide substrate and polishing method for silicon oxide substrate
WO2026179165A1